2020
DOI: 10.3390/ijgi9030149
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of a Recreational-Grade Interferometric Sonar for the Bathymetric Survey and Monitoring of the Drava River

Abstract: Sonar survey of shallow water bodies has challenged scientists for a long time. Although these water courses are small, still they have an increasing ecological, touristic and economical role. As maritime sonars are non-ideal tools for shallow waters, the bathymetric survey of these rivers has been taken with cross-sectional methods. Due to recent developments, interferometric surveying technology have also burst into the market of recreational-grade fish-finders. The objective of the current study was the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The Trimble RTK GNSS equipment is positionally accurate with a horizontal accuracy of 1-2 cm, while Pixhawk Cube Orange GNSS RTK internal to the vessel can be as accurate as 3 cm, and the Lowrance Elite Ti2 claims 20 m RMS positioning accuracy [54]. A simple preliminary experiment comparing the three devices observed that the Lowrance GPS can waiver from the RTK GNSS devices by 1.5-3 m. However, the uncorrected GPS is, in principle, mostly translated horizontally and still captures the relative path taken by the vessel [55]. To compare the ground-truth survey points to the sonar depth data, both datas were imported into ArcGIS pro.…”
Section: Resultsmentioning
confidence: 99%
“…The Trimble RTK GNSS equipment is positionally accurate with a horizontal accuracy of 1-2 cm, while Pixhawk Cube Orange GNSS RTK internal to the vessel can be as accurate as 3 cm, and the Lowrance Elite Ti2 claims 20 m RMS positioning accuracy [54]. A simple preliminary experiment comparing the three devices observed that the Lowrance GPS can waiver from the RTK GNSS devices by 1.5-3 m. However, the uncorrected GPS is, in principle, mostly translated horizontally and still captures the relative path taken by the vessel [55]. To compare the ground-truth survey points to the sonar depth data, both datas were imported into ArcGIS pro.…”
Section: Resultsmentioning
confidence: 99%
“…In navigable rivers, river bathymetry is typically measured with single beam or multi-beam sonar on-board manned or unmanned vessels (Bio et al, 2020;Halmai et al, 2020;Leyland et al, 2017;Specht et al, 2020;Stateczny et al, 2019;Young et al, 2017). However, sonar systems have limitations in measuring very shallow depths due to surface clutter and multipath effects (Albright Blomberg et al, 2013); furthermore, the accuracy of sonar signi cantly degrades in vegetated rivers (Helminen et al, 2019), indeed the high level of re ection of sound waves from the vegetation can result in depth measurements within vegetation canopy (Sabol, 2002).…”
Section: Sonarmentioning
confidence: 99%
“…In navigable rivers, river bathymetry is typically measured with single beam or multi-beam sonar on-board manned or unmanned vessels (Bio et al, 2020;Halmai et al, 2020;Leyland et al, 2017;Specht et al, 2020;Stateczny et al, 2019;Young et al, 2017). However, sonar systems have limitations in measuring very shallow depths due to surface clutter and multipath effects (Albright Blomberg et al, 2013); furthermore, the accuracy of sonar signi cantly degrades in vegetated rivers (Helminen et al, 2019), indeed the high level of re ection of sound waves from the vegetation can result in depth measurements within vegetation canopy (Sabol, 2002).…”
Section: Sonarmentioning
confidence: 99%